2019
DOI: 10.1021/jacs.9b03113
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Aldehydes to Branched or Linear Ketones via Regiodivergent Rhodium-Catalyzed Vinyl Bromide Reductive Coupling–Redox Isomerization Mediated by Formate

Abstract: A regiodivergent catalytic method for direct conversion of aldehydes to branched or linear alkyl ketones is described. Rhodium complexes modified by P t Bu 2 Me, catalyze formate-mediated aldehyde-vinyl bromide reductive coupling-redox isomerization to form branched ketones. Use of the less strongly coordinating ligand, PPh 3 , promotes vinyl-to allylrhodium isomerization en route to linear ketones. This method bypasses the 3-step sequence often used to convert aldehydes to ketones involving the addition of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…In theory, the most inexpensive path to achieving this is through electroreductive means, and three reports point to this proof of concept as highlighted in Figure 1B. [9][10][11] Grigg showed that a Pd-variant of the NHK could be achieved in a divided-cell setup, 9 whereas Tanaka 10 and Durandetti 11 demonstrated galvanostatic means for achieving NHK reactions with Ni catalysts. The issues with these early studies were the poor substrate scope, difficult setups (divided cell or reference electrodes), and the use of expensive electrodes such as Pt.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In theory, the most inexpensive path to achieving this is through electroreductive means, and three reports point to this proof of concept as highlighted in Figure 1B. [9][10][11] Grigg showed that a Pd-variant of the NHK could be achieved in a divided-cell setup, 9 whereas Tanaka 10 and Durandetti 11 demonstrated galvanostatic means for achieving NHK reactions with Ni catalysts. The issues with these early studies were the poor substrate scope, difficult setups (divided cell or reference electrodes), and the use of expensive electrodes such as Pt.…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, entries 1 and 2 were problematic due to the requirement of slow syringe pump addition of the aryl halide along with the need for careful control of potential (reference electrode). Although the yield was low, the Tanaka conditions 10 (entry 4) benefitted from a more practical procedure with a simple undivided cell setup and were therefore chosen as a framework from which to optimize. The development of a synthetically useful e-NHK reaction required exploration of five main parameters: (1) oxophilic additives, (2) ligands for Ni, (3) Ni source, (4) Cr source, and (5) electrochemical parameters (electrode, electrolyte, current).…”
Section: Electrochemical Nozaki-hiyama-kishi Coupling: Development and Scopementioning
confidence: 99%
See 1 more Smart Citation
“…Aldehyde C–H bonds can be directly functionalized by coupling them with a carbon electrophile, such as readily available aryl and alkenyl halides under palladium catalysis, as an ideal way to synthesize ketones, which exhibit ubiquitous functionalities with important applications in pharmaceuticals, natural products, organic materials, photosensitizers, flavors, and fragrances. Because of their high bond dissociation energy and low acidity, the aldehyde C–H bond structure is particularly challenging to alter under palladium catalysis. Kuninobu and Kanai recently reported palladium-catalyzed aldehyde C–H arylation at high temperature, wherein a newly designed ligand was used to facilitate deprotonative C–H functionalization of the aldehyde C–H bond on a Pd II center to achieve a variety of ketone syntheses . However, this protocol exploiting the picolinamide ligand gave diminishing yields of aliphatic aldehydes featuring C–H bonds of high p K a .…”
mentioning
confidence: 99%
“…Krische has demonstrated elegant contributions on the linkage of alcohols/carbonyls with unsaturated C−C bonds. [30][31][32] Bruneau et al have achieved β-C(sp 3 )−H alkylation of N-alkyl cyclic amines. [33][34] The Li group has converted phenols into synthetically useful amines.…”
Section: Introductionmentioning
confidence: 99%